A single endoplasmic reticulum aminopeptidase-1 protein allotype is a strong risk factor for Behçet's disease in HLA-B*51 carriers. Issue 12 (23rd May 2016) - Takeuchi, Masaki; Ombrello, Michael J; Kirino, Yohei; Erer, Burak; Tugal-Tutkun, Ilknur; Seyahi, Emire; Özyazgan, Yilmaz; Watts, Norman R; Gül, Ahmet; Kastner, Daniel L; Remmers, Elaine F
Abstract : Introduction: Endoplasmic reticulum aminopeptidase-1 (ERAP1) protein is highly polymorphic with numerous missense amino acid variants. We sought to determine the naturally occurring ERAP1 protein allotypes and their contribution to Behçet's disease. Methods: Genotypes of all reported missense ERAP1 gene variants with 1000 Genomes Project EUR superpopulation frequency >1% were determined in 1900 Behçet's disease cases and 1779 controls from Turkey. ERAP1 protein allotypes and their contributions to Behçet's disease risk were determined by haplotype identification and disease association analyses. Results: One ERAP1 protein allotype with five non-ancestral amino acids was recessively associated with disease (p=3.13×10 −6, OR 2.55, 95% CI 1.70 to 3.82). The ERAP1 association was absent in individuals who lacked HLA-B*51. Individuals who carry HLA-B*51 and who are also homozygous for the haplotype had an increased disease odds compared with those with neither risk factor (p=4.80×10 −20, OR 10.96, 95% CI 5.91 to 20.32). Discussion: The Behçet's disease-associated ERAP1 protein allotype was previously shown to have poor peptide trimming activity. Combined with its requirement for HLA-B*51, these data suggest that a hypoactive ERAP1 allotype contributes to Behçet's disease risk by altering the peptides available for binding to HLA-B*51.